Foundations of visual communication how visuals appear in daily life - Eriksson, Yvonne; Göthlund, Anette (Routledge, Taylor & Francis Group, 2023)
"Drawing upon theories from visual studies, critical visual culture studies, and cognitive psychology, and with a special focus on gender and ethnicity, this book gives students a theoretical foundation for future work as visual communicators. The book takes a closer look at the interwoven character of perception and reception that is present in everyday visual encounters. Chapters present a wide variety of visual examples from art history, digital media, and the images we encounter and use in our daily lives. With the tools to understand how images and text make meaning, students are thus prepared to better communicate through visual media. This book serves as a main or supplementary text for visual communication or visual culture courses"--
Includes bibliographical references and index
Keywords: Visuelle Kommunikation; Visual communication; Visual communication / Methodology